ANGULAR MOMENTUM CHANGES IN ECLIPSING BINARY STARS OF DIFFERENT TYPES - Karetnikov, V. G. (Одеські астрономічні публікації, 2017)
. Based on the characteristics on 303 eclipsing binary stars we calculated the angular moments and those dependence from the stellar masses. We got the clear correlations when divided the stars on the groups with different masses and orbital periods. It was shown, that the angular moment successively descreases during passing from MS- through CE- towards to SD- system stars and increasing the speed of changes. The maximal values of changes of the speed of changes was found for systems of small masses and periods. It was discussed the unsingle dependence in CE systems of small masses and periods.